2010
DOI: 10.1007/s10499-010-9320-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation in Kappaphycus alvarezii using micro-particle bombardment: a potential strategy for germplasm improvement

Abstract: This study investigated the delivery of a SV40 promoter driving lacZ gene into cells of Kappaphycus alvarezii using particle bombardment. Thallus pieces 0.5-0.8 mm in diameter and 1 cm in length were prepared as gene recipients. Bombardment parameters of 450 psi (rupture pressures) 9 6 cm (particle travel distances), 650 psi 9 6 cm, 1,100 psi 9 6 cm and 1,100 psi 9 9 cm were used. A significant increase in transformation efficiency from about 33% under the rupture pressure of 450 psi to 87% at 650 psi was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…This is not the first reported case of gold particles penetrating the thallus exterior cells to allow transgene expression in the underlying cells. Wang et al (2010) reported that when a rupture disc pressure of 650 psi was used in the bombardment of K. alvarezii, transgene expression could be identified in the epidermal cells as well as in the medullary cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not the first reported case of gold particles penetrating the thallus exterior cells to allow transgene expression in the underlying cells. Wang et al (2010) reported that when a rupture disc pressure of 650 psi was used in the bombardment of K. alvarezii, transgene expression could be identified in the epidermal cells as well as in the medullary cells.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, research was carried out on transient expression of reporter genes under the control of promoters that had been used for similar purposes in higher plants and unicellular algae (Qin et al, 2004). Transient gene expression has been reported in Kappaphycus alvarezii explants (Kurtzman and Cheney, 1991;Wang et al, 2010), Porphyra miniata protoplasts (Kübler et al, 1994), Porphyra yezoensis protoplasts and explants (Kuang et al, 1998;Mizukami et al, 2004), Ulva lactuca protoplasts (Huang et al, 1996) and Gracilaria changii explants (Gan et al, 2003). In many of these cases, transient gene expression was achieved using the Cauliflower mosaic virus (CaMV) 35S promoter.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic engineering techniques have therefore been expected to improve seed stocks of seaweeds (Hallman, 2007). In fact, transgenic reasearch have been conducted on Laminaria japonica using β-glucuronidase (Li et al, 2009), Kappaphycus alvarezii using LacZ gene (Wang et al, 2010) and Gracilaria changii using LacZ gene as reporter (Huddy et al, 2012;Gan et al, 2003). In Wang et al study, Kappaphycus alvarezii transgenic was produced by micro-particle bombardment method (Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the selection of seedlings from the same population for several years and the overexploitation of natural beds have diminished the diversity and genetic superiority of this species. As a consequence, low resistance to stress and decrease in growth rates, as well as a reduction in yield and quality of phycocolloids are reported (Dawes and Koch 1991;Hurtado and Biter 2007;Wang et al 2010). These conditions, coupled with worldwide increase of carrageenan consumption, have motivated the study of strains with higher quality and variability (Ask and Azanza 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2010) tested methods with micro-particle bombardment for gene insertion to produce transgenic strains of K. alvarezii. According to them, transformants were produced, suggesting that this method may be useful in improving germplasm resources.…”
Section: Introductionmentioning
confidence: 99%